2023
DOI: 10.1002/ejic.202300260
|View full text |Cite
|
Sign up to set email alerts
|

Computational (DFT) and Experimental (NMR) Study of the Chelation of an Iridium Hyperpolarization Transfer Catalyst by Amino Acids

Mathijs J. Bouma,
Ruud L. E. G. Aspers,
Marco Tessari
et al.

Abstract: Non‐hydrogenative Para‐Hydrogen Induced Hyperpolarization (nhPHIP) is a Nuclear Magnetic Resonance (NMR) hyperpolarization technique which has experimentally been used to analyze complex biological samples containing amino acids using the Ir‐IMes hyperpolarization transfer catalyst. A computational study based on Density Function Theory (DFT) was performed on all relevant stereoisomers of [Ir(H)2(IMes)(AA)(Py)] (with AA=glycine, alanine, valine; Py=pyridine), for which R/S chirality and orientation of the amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Calculations showed that the binding pattern with N-terminus in ax and C-terminus oxygen in eq plane is the energetically favored bidentate l -Ala-catalyst-complex, in agreement with experimental results from Tessari group 28 as well as with the recent gas-phase DFT study, 34 further confirming strong prevalence of the bidentate ax–eq binding mode for alanine (see SI_DFT†). Additionally, according to DFT, there are two bidentate binding topologies of higher energy: reversed ax–eq and eq–eq (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Calculations showed that the binding pattern with N-terminus in ax and C-terminus oxygen in eq plane is the energetically favored bidentate l -Ala-catalyst-complex, in agreement with experimental results from Tessari group 28 as well as with the recent gas-phase DFT study, 34 further confirming strong prevalence of the bidentate ax–eq binding mode for alanine (see SI_DFT†). Additionally, according to DFT, there are two bidentate binding topologies of higher energy: reversed ax–eq and eq–eq (Fig.…”
Section: Resultssupporting
confidence: 85%